miR-34a-5p as molecular hub of pathomechanisms in Huntington's disease - Martin Hart; Caroline Diener; Laetitia Lunkes; Stefanie Rheinheimer; Lena Krammes; Andreas Keller; Eckart Meese (BMC, 2023)
Abstract Background Although a pivotal role of microRNA (miRNA, miR) in the pathogenesis of Huntington's disease (HD) is increasingly recognized, the molecular functions of miRNAs in the pathomechanisms of HD await further elucidation. One of the miRNAs that have been associated with HD is miR-34a-5p, which was deregulated in the mouse R6/2 model and in human HD brain tissues. Methods The aim of our study was to demonstrate interactions between miR-34a-5p and HD associated genes. By computational means we predicted 12 801 potential target genes of miR-34a-5p. An in-silico pathway analysis revealed 22 potential miR-34a-5p target genes in the KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway "Huntington's disease". Results Using our high-throughput miRNA interaction reporter assay (HiTmIR) we identified NDUFA9, TAF4B, NRF1, POLR2J2, DNALI1, HIP1, TGM2 and POLR2G as direct miR-34a-5p target genes. Direct binding of miR-34a-5p to target sites in the 3'UTRs of TAF4B, NDUFA9, HIP1 and NRF1 was verified by a mutagenesis HiTmIR assay and by determining endogenous protein levels for HIP1 and NDUFA9. STRING (Search Tool for the Retrieval of Interacting Genes/Proteins) analysis identified protein-protein interaction networks associated with HD like "Glutamine Receptor Signaling Pathway" and "Calcium Ion Transmembrane Import Into Cytosol". Conclusion Our study demonstrates multiple interactions between miR-34a-5p and HD associated target genes and thereby lays the ground for future therapeutic interventions using this miRNA.